PERSEPSI KELOMPOKTANI/PETANI, PENYULUH PERTANIAN LAPANGAN (PPL), DAN PENGECER RESMI DALAM PENYALURAN PUPUK BERSUBSIDI DI KABUPATEN LOMBOK BARAT - Hasan, Hasan (Valid Jurnal Ilmiah, 2017)
Purpose of this study was to determine emperis Perception Group/Farmers, the Agricultural Extension Workers (PPL) and on the distribution of Subsidized Fertilizer Retailers. The research hypothesis testing using Friedman techniques with the intention to test three group differing perceptions of distribution og subsidized fertilizer. Research shows that the perception of group/farmer/and agricultural Exention, react different to the distribution of responsibilitas beyond or outside the ragion are found, farmers are still no fully registered in the Definitive Plan of Group (RDKK).  Warning implications of this study provide the retailer, group/farmer/as well as the Agricultural Extension workers (PPL) to comply with the rules og the minister of agricultural and trade minister